CFL Touching Down Back in Ottawa: Exploring Corporate Image and Brand Equity Prior to Entry - Desjardins, Élise (Université d'Ottawa / University of Ottawa, 2012)
This mixed method research evaluates corporate image theory and its impact on assets of brand equity. It consists of a single case study of a CFL franchise coming back to a market that has experienced two failed franchises. The first phase involved the collection of archival material and the execution of semi-structured interviews. Through content analysis, four higher order themes emerged: the importance of Football Tradition, the need for a new Sport Facility, and the importance placed on both Identity and Brand Awareness. These themes denoted the importance of history and tradition for a franchise making its debut in a new, yet pre-existing market. The second phase involved survey research via an online method. Demographic data was compiled and analyzed to understand the various market segments that this franchise should be targeting as future fans. The findings suggest that this team should find a new name and a new logo.
Keywords: CFL; CFL Ottawa; CFL Corporate Image; CFL Brand Equity